Convergence Rates for Generalized Descents - Pike, John (The Electronic Journal of Combinatorics, 2011)
d-descents are permutation statistics that generalize the notions of descents and inversions. It is known that the distribution of d-descents of permutations of length n satisfies a central limit theorem as n goes to infinity. We provide an explicit formula for the mean and variance of these statistics and obtain bounds on the rate of convergence using Stein’s method.